Target Antigens of Membranous Nephropathy With Syphilis Infection - Liyin Zhang; Minfang Zhang; Qionghong Xie; Yongxiang Wang; Zhaohui Ni; Shaojun Liu; Wenyan Zhou (Kidney International Reports)
Introduction: Membranous nephropathy (MN) is the most common cause of proteinuria in syphilis, and neuron-derived neurotrophic factor (NDNF) was recently demonstrated to be the target antigen in syphilis-associated MN. However, the prevalence and clinicopathological characteristics of both NDNF-positive and NDNF-negative MN in Chinese individuals with syphilis infection still remain unknown. Methods: A retrospective study was conducted in 17 patients with MN with history of syphilis infection. The intensity and distribution of NDNF staining, as well as phospholipase A2 receptor (PLA2R) and neural epidermal growth factor-like 1 protein (NELL-1) staining in renal biopsies were assessed. Results: Among the 11 patients with MN with active syphilis infection, positive NDNF staining was shown in 5 patients (46%). The remaining 6 patients demonstrated negative NDNF staining. Of these, 5 patients were PLA2R-positive and 1 patient was PLA2R-negative and NELL-1-negative. Antibiotics were also effective in 3 NDNF-negative patients, suggesting the possibility of syphilis-associated MN. Therefore, the histological positivity rate of NDNF was 63% (5/8 patients) in syphilis-associated MN. In addition, positive NDNF antibody was first confirmed in the serum of 1 patient with NDNF-associated MN. NDNF staining was negative in all 6 patients with MN with previous syphilis infection. Conclusion: Nearly half of the patients with active syphilis infection and MN were NDNF-positive in our study. Positive NDNF staining favors syphilis-associated MN. Circulating anti-NDNF antibody can be detected in the patient’s serum sample. In addition, PLA2R or other unknown antigenic protein may also be the target antigens for syphilis-associated MN in Chinese population.